Governing Vitalities and the Security State. (October 2014) - Kearns, Gerry
The techniques by which states regulate life are both spatial and geopolitical. Foucault wrote of a broad transition from a state concern with territory focused on regulating threats such as famine and epidemics, to a modern concern with population that prioritised instead a set of everyday dangers that were to be averted by continual action for and upon individuals. In this paper I argue that territoriality is more geopolitical in character and more continually significant than Foucault suggested. This geopolitics implicates a global political economy and forms of imperialism and colonialism occluded by Foucault's state-centric rather than states-centric approach.